Pengaruh Imbangan Susu UHT dan Jus Kurma terhadap Karakteristik Kimia (pH dan Kadar Serat) dan Karakteristik Organoleptik Produk Susu Kurma - Athar, Rahma Safira; Wulandari, Eka; Utama, Dicky Tri (Jurnal Teknologi Hasil Peternakan, 2023)
UHT milk is a processed milk product that has a lot of nutritional content in it and is a product that is widely consumed by the public. UHT milk is more beneficial when combined with dates because dates contain various kinds of nutrients that UHT milk does not have. This study aims to find out what percentage of date palm juice concentration will produce the best pH value, fiber content and preference value. This research was conducted experimentally with a completely randomized design (CRD) using 3 treatments and 6 replications with the percentage of date juice consisting of P1 (10%), P2 (20%) and P3 (30%). The research data were analyzed using analysis of variance and Duncan's multiple range test for pH and fiber content parameters, while the Kruskal Wallis test and Mann Whitney test were used for preference parameters. The results showed that the addition of date palm juice affected the pH value and fiber content. The addition of date juice also affects preferences, namely taste, but does not affect color, aroma, texture and overall. The addition of 30% of date juice is preferably acceptable to consumers and in terms of a pH value of 6.65 and a fiber content of 5.62% has the best results.